Changes in Parents’ Home Learning Activities With Their Children During the COVID-19 Lockdown – The Role of Parental Stress, Parents’ Self-Efficacy and Social Support - Oppermann, Elisa; Cohen, Franziska; Wolf, Katrin; Burghardt, Lars; Anders, Yvonne (Frontiers in Psychology, 2021)
As a result of the abrupt closures of daycare centers in Germany due to the COVID-19 pandemic, parents' ability to provide learning opportunities at home became all the more important. Building on the family stress model, the study investigates how parental stress affected changes in parents' provision of home learning activities during the lockdown, compared to before the lockdown. In addition, the study considers parental self-efficacy and perceived social support as protective factors that may play important roles in disrupting the negative effects of stress. Data stems from a nation-wide survey of 7,837 German parents of children ages 1-6 years, which was conducted in Spring 2020 during the first wave of COVID-19 infections and at a time of strict restrictions in Germany. Results revealed that parental stress was negatively related to changes in the provision of home learning activities. Parental self-efficacy and an intact social support system were protective of parental stress during the lockdown. Additionally, parental self-efficacy and – to a larger extend – perceived social support interacted with parental stress in the relation to changes in the provision of home learning activities. Specifically, self-efficacy and perceived social support acted as protective factors that buffered the negative influence of stress on parents’ ability to provide educational activities for their children at home. These results have important implications for supporting families with young children during challenging times, such as the COVID-19 pandemic and the temporary closure of daycare centers.